A stereo-electronic interpretation of a challenging orthoamide Overman rearrangement rationalized by molecular modelling. (24th August 2022) - Juvin, Judith; Malherbe, Victor; Belhomme, Marie-Charlotte; Castex, Stéphanie; Martinez, Agathe; Khartabil, Hassan; Haudrechy, Arnaud
Abstract : The Overman rearrangement difficulties are tentatively explained using stereo-electronic considerations, helping chemists to understand their troubles in this process. Abstract : The Overman rearrangement is a very useful C–N bond forming reaction described for the first time in 1974. This transformation allows a chirality transfer with an excellent predictible induction, starting from a configurationally pure allylic alcohol, yielding in only one step an amide moiety, via a [3, 3]-sigmatropic rearrangement of an intermediate imidate. A recent valuable extension was developed by Chida and co-workers on orthoamide structures starting from allylic vicinal diols, avoiding time consuming protections. However, this attractive modified approach suffers generally from elevated temperatures, long reaction times and sometimes disappointing yields. To bridge this gap, we have carried out a combined experimental and theoretical study with the aim of elucidating the structures and the reactivities of these orthoamides. In order to rationalize the experimental results, it was first fundamental to identify the actual reactive species. The reactivity of these orthoamides was then investigated. Theoretical calculations using density functional theory (wB97X-D/Def2TZVP method) were then performed in the gas phase at 453 K to characterize the relevant chemical species (conformers of orthoamide diastereoisomers, prereactive complexes, and transition states structures) and to estimate the free energies of activation. The role of temperature has also been taken into consideration at 298 K and 373 K in comparison with 453 K. A major contribution of the theoretical part of this study has been to show that the reactivity of orthoamides in the Overman rearrangement crucially depends on diastereoisomers present in the reaction media. Molecular simulation has allowed us to clarify the reasons behind the temperature requirements and the reaction time, tentatively helping chemists to understand their troubles in orthoamide Overman rearrangement.